2009
DOI: 10.1177/1753465809349741
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the tachykinin NK2 receptor antagonist MEN11420 (nepadutant) on neurokinin A-induced bronchoconstriction in asthmatics

Abstract: In conclusion, the tachykinin NK(2) receptor antagonist nepadutant significantly inhibits bronchoconstriction induced by neurokinin A in patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…However, based on abstract, only seven studies appeared to meet the inclusion criteria and their full text was obtained (Figure 1). Therefore, we included 7 studies comprising the use of five tachykinin receptors antagonists: NK-2 in two [10-12], NK-1/NK-2 in four [11,13-15] and NK-1/NK-2/NK-3 in other one [16], referring to a total of 98 subjects (Table 1). All studies used different doses of tachykinin receptors antagonists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on abstract, only seven studies appeared to meet the inclusion criteria and their full text was obtained (Figure 1). Therefore, we included 7 studies comprising the use of five tachykinin receptors antagonists: NK-2 in two [10-12], NK-1/NK-2 in four [11,13-15] and NK-1/NK-2/NK-3 in other one [16], referring to a total of 98 subjects (Table 1). All studies used different doses of tachykinin receptors antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding treatment dosages, 5 studies used single-doses [11-13,15,16] while in 2 studies doses of antagonists were given during 2 and 9 consecutive days [10,14]. Antagonists were administered by inhalation in 3 studies [10,15,16] and orally in 4 studies [11-14]. None of the studies reported changes in asthma symptoms as an outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, release of tachykinins by the excitation of these nerve systems is thought to be involved in the pathogenesis of airway allergy in humans (14,15). Because those factors are produced in the airway tissues during inflammatory responses, developing therapy that blocks the tachykinin-dependent signaling cascade might be beneficial for the treatment of allergic inflammation (16)(17)(18).…”
mentioning
confidence: 99%
“…Recent articles indicated that SP regulates the function of various leukocytes, such as vascular endothelial growth factor secretion from mast cells (19), cytotoxicity of NK cells (20), cytokine production by monocytes and T cells (21,22), induction of chemokine or chemokine receptor of macrophages (23,24), and Ag presentation of dendritic cells (DCs) (25). In contrast, NKA is known to control various vital responses, such as airway contraction, vasodilatation, and vascular permeability, in humans (15,16,26). However, the function of NKA in the immune system is less-well defined compared with the role of SP.…”
mentioning
confidence: 99%
“…The NK-2 receptor exhibits the highest affinity for neurokinin A. Neurokinin A is known to control various vital responses in humans, such as airway contraction, vasodilatation, and vascular permeability [137]. The function of neurokinin A in the immune system is less well defined compared with the role of substance P. One study reported that neurokinin A stimulation induced mRNA expression of type I interferons, upregulated expression of MHC class II molecules, and antigen presentation by DC, thereby enhancing DC function [138] and subsequently inducing CD4 + and CD8 + T cell responses.…”
Section: Regulation Of the Immune System By The Neuroendocrine Sysmentioning
confidence: 99%